Improving Students' Problem Solving Skills in Learning Problem Based Learning Integrated with Predict, Observe, Explain Model on Global Warming Material - Ismiandini, Rifa; Karim, Saeful; Saepuzaman, Duden (Jurnal Penelitian Pembelajaran Fisika, 2024)
In the following study, the aim is to analyze the improvement of students' problem solving skills in learning activities with problem-based learning models integrated with predict, observe, explain models, especially for global warming material. The study was conducted using quantitative methods with 33 participants of class X students at one of the SMAN Cimahi City which was determined based on convenience sampling technique. The data collected in the following study was conducted through a problem solving skills test instrument in the form of pretest and posttest questions. To analyze the data obtained, using N-Gain testing on the data from the pretest and posttest scores. The results showed that each aspect of problem solving skills experienced a moderate increase. In addition, the acquisition of hypothesis testing proves that there is a difference in the application of the PBL-POE model in improving students' problem solving skills.